On a dramaturgical marginalium of the 1920s - M. V. Akhmetova (Шаги, 2023)
The paper analyzes anonymous handwritten corrections in a copy of a propagandist play, “Darkness” (T’ma, 1927), by T. M. Martynov. The author suggests that the anonymous editor worked in the Nizhny Novgorod Krai’s Department of Public Education (Nizhkraiono), which was responsible for overseeing theatrical work. The author distinguishes factographic, stylistic and ideological emendations. The latter include the elimination of derogatory remarks about the main character (a peasant woman) in the speech of positive characters, as well as a radical change in the ending. In the new version, the heroine’s husband does not abandon her, but only threatens to do so unless she learns to read and write, and asks the village healers for help. The author concludes that the handwritten corrections corresponded to two key tenets of the epoch. According to the first one, the peasants were not as responsible for their ignorance as was the “old regime”, and thus their misdeeds deserved indulgence (this idea, in particular, was reflected in so called agitation trials). On the other hand, criticism of the backwardness of the Soviet countryside should be accompanied by demonstration of the peasantry’s transition to a new life; this idea can be observed in numerous guides for sel’kors (‘village correspondents’). Therefore, the corrections to the play smoothed out the critical angles of the original play and suggested its approximation to the current ideological attitudes.